The Concept Of English As A Foreign Language (Efl) In The Perspective Of Language Education: A Literature Review On Learning Orientation, Classroom Practices, And AI Technology Integration In Indonesia - Fauzen, Fauzen; Wildona Zumam (Amandemen: Journal of Learning, Teaching and Educational Studies, 2026)
This study aims to map the conceptual developments and key issues in English as a Foreign Language (EFL) learning from a language education perspective, particularly in the Indonesian context, which is increasingly influenced by the dynamics of English as a Lingua Franca (ELF), bilingual language practices in the classroom, demands for strengthening 21st-century competencies, and the accelerated use of artificial intelligence (AI) technologies such as ChatGPT. The research uses a qualitative approach with a literature study design through content analysis and thematic synthesis of selected literature from the period 2022–2025. The synthesis results show five main themes: (1) reorientation of EFL objectives towards cross-variety communication and ELF awareness; (2) negotiation of the medium of instruction and use of L1 in EFL classrooms; (3) dimensions of values and character in teaching materials; (4) the quality of academic interaction through linguistic politeness; and (5) the integration of multimodal media and AI (including ChatGPT), which presents opportunities for personalized learning as well as ethical and pedagogical risks. The findings confirm that a contextual understanding of EFL must be supported by micro-pedagogical policies in the classroom, the strengthening of digital literacy and AI, and learning designs that continue to place communicative goals, critical thinking, and character building as core outcomes. This study contributes to providing a conceptual map that can be used as a reference for curriculum development, teacher training, and the EFL research agenda in Indonesia.